Analysis of 20th Century Extended Guitar Techniques on Selected Works - Barış Önder (Konservatoryum)
In the 20th century, the search for meaning in music and other areas of art led to the emergence of various art movements. In the 20th century, composers resorted to extended techniques and modern notation in order to create the special effects they wanted. Especially composers of the period; Karlheinz Stockhausen, György Ligeti, Iannis Xenakis, Krzysztof Penderecki, John Cage, etc. included avant-garde elements and extended instrument techniques in their works. In this study, the influence of the artistic understanding of the period on guitar music and guitar composers is handled with examples of works by 20th century composers. The aim of the study is to bring the reflections of the extended instrument techniques, which started to be used in the 20th century period, on the guitar field and the new guitar techniques developed in the 20th century to the literature by analyzing the works. The inclusion of this study in the guitar literature is important in terms of learning the new techniques in the works of 20th century guitar music composers and obtaining new sound colors with the techniques used. In this study, extended guitar techniques have been analyzed on Roland Dyens “Libra Sonatine” “A Night in Tunisia” “Fantasie”, Paulo Bellinati “Jongo”, Leo Brouwer “La Espiral Eterna”, Alberto Ginastera “Sonata”, Nikita Kushkin “Usher Valse”, Francis Kleynjans “A L’aube du Derneir Jour”.